Pengaruh Motivasi Ekstrinsik Dan Disiplin Kerja Terhadap Kinerja Pegawai DPPKD Provinsi Banten UPT Cikande Kabupaten Serang - Arlin Febriani, H. Wawan Prahiawan, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
The purpose of this research was to determine the influence of Extrinsic Motivation and Dicipline Of Working On Employee Performance. Kind of research is quantitative research technique and the use of survey. This study uses literature and field research such as interviews, observation and questionnaires.